Rural financial savings mobilization in Sri Lanka: Bottlenecks and reform proposals - Bernhard Fischer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
The objective of the following study is to evaluate rural deposit mobilization programmes in Sri Lanka, to identify major bottlenecks in the national savings system, and to provide recommendations for improving rural (financial) savings mobilization for financing rural development. Major trends in aggregate and financial savings of the economy of Sri Lanka are given in the following section of the Introduction. Chapter II reviews the incentive system and institutional framework for (rural) deposit mobilization by focusing on interest rate policies, access to banking facilities, and the appropriateness of savings instruments. Rural financial savings by type of financial institution are examined in Chapter III. The scattered empirical evidence of the performance of informal savings (and credit) activities is elaborated in Chapter IV. In Chapter V, reform proposals for mobilizing rural savings for rural development are provided, based on an evaluation of major bottlenecks in savings mobilization (and credit supply) in rural areas. The discussion focuses on the preferential status of the National Savings Bank, the insufficient link between savings and lending activities, the problem of savings outflows from rural areas and policy options towards the informal (financial) sector.
Keywords: 330